Smartphone restriction modulates intrinsic neural activity in problematic smartphone users: evidence from resting-state fMRI - Haage, Sophie H.; Schmitgen, Mike; Henemann, Gudrun Maria; Koenig, Julian; Otte, Marie-Luise; Bach, Patrick; Wolf, Nadine D.; Wolf, Robert Christian (Addictive behaviors, 2026)
Problematic smartphone use (PSU) has been associated with withdrawal-like symptoms and altered intrinsic neural activity (INA). While previous studies suggest that PSU affects brain function, little is known about how INA is modulated by smartphone restriction. This longitudinal fMRI study investigated group- and time-dependent changes in resting-state INA following short-term smartphone deprivation. 36 participants (aged 18-29; 22 female) were categorized into PSU (n = 19) and non-PSU (n = 17) groups using the Smartphone Addiction Scale-Short Version (SAS-SV). Resting-state fMRI scans were obtained before and after a 72-hour period of smartphone restriction. Psychometric measures included the Mannheim Craving Scale (MaCS) and the Smartphone Addiction Inventory (SPAI). A significant group-by-time interaction revealed INA changes in the left inferior frontal gyrus, bilateral posterior cingulate cortex, right middle frontal and precentral gyri, and left calcarine cortex. INA increased over time in the non-PSU group but decreased in the PSU group in prefrontal and cingulate areas. In contrast, sensorimotor and occipital regions showed increased INA over time in PSU individuals. Associations between neural activity and MaCS scores indicated that greater craving was linked to reduced INA in the posterior cingulate cortex. Within the PSU group, higher smartphone-use severity, as measured by the SPAI, was associated with altered INA in occipital, parietal, and cerebellar regions. These findings suggest PSU is linked to distinct and state-dependent neurofunctional alterations that may reflect withdrawal-related processes and maladaptive reward and cognitive control mechanisms.